Anemia in Pregnancy: Study Phenomenology - Rina Doriana Pasaribu; Evawany Aritonang; Etti Sudaryati; Fikarwin Zuska (Karger Publishers, 2023)
Introduction: The prevalence of anemia in pregnant women in Indonesia remains high. This condition is concerning because the government has run a program of giving iron tablets to pregnant women since 1970. This study aimed to determine socioenvironmental factors that cause anemia in pregnant women. Methods: This qualitative research used phenomenological methods. In-depth interviews were conducted with 20 mothers with anemia and 12 focus group discussion (FGD) informants. Qualitative data analysis was applied to analyze the data. Results: The study found three factors: anemia in the preconception period, diets that cause a lack of iron consumption, and knowledge and consumption of iron tablets in pregnant women. Anemia in pregnant women is a continuous cycle of anemia which begins in the preconception period. Adolescent eating behavior and supplementation programs for pregnant women integrated with antenatal care are still problematic. Discussion and Conclusion: The findings of this study provide important information for preventing anemia in pregnant women, increasing counseling, and evaluating the implementation of iron supplementation in pregnant women. The policy of administering iron tablets to pregnant women to prevent anemia is not effective in reducing the prevalence of anemia. This government policy must be accompanied by a community movement program because the findings of this study show the problems that exist in the individual factors of the mother.